ANALISIS PENGELOLAAN KEUANGAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI SEKOLAH MENENGAH ATAS NEGERI OLAHRAGA SIDOARJO (SMANOR) - Tabita Fristelina Mogot (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
The School Operational Fund Assistance Program (BOS) is a strategy in supporting the compulsory education program. BOS funding assistance is provided for school operational costs with the aim of freeing education costs for underprivileged students and easing the burden of students in the future. The purpose of this study is to analyze School Financial Management at the high school of sidoarjo sport (SMANOR). The process of Financial Management in this study includes planning, preparation, and also budget reporting whose estimates have not been fully carried out using the principles of school financial management, namely efficiency and fairness. In this study the authors used a qualitative approach. The techniques used are documentation, observation and interviews. The results showed that school financial management was carried out based on the planning for the management of BOS funds for the 2018-2019 school year, starting from the process of preparing the Activity Plan and School Budget, as well as the preparation of the Budget Plan (RAB) and also the applicatin for use at the end was carried out by means of bookkeeping. The supporting factor in implementing the program is cooperation between teacher employees, while the inhibiting factors for the management of BOS funds are too large of funds and obstacles in making reports on the use of BOS funds due to the limited amount of time and the lack of knowledge of the treasurer in managing financial finance.